HUBUNGAN HYGIENE PERORANGAN DAN PEMAKAIAN ALAT PELINDUNG DIRI DENGAN KELUHAN GANGGUAN KULIT PADA PEKERJA PENGUPAS UDANG DI KELURAHAN PEKAN LABUHAN KECAMATAN MEDAN LABUHAN TAHUN 2012 - Faddilatul Aisyah; Devi Nuraini Santi; Indra Chahaya (Lingkungan dan Kesehatan Kerja, 2013)
Relatian between personal hygiene and use of safety equipment with complains of skin disorder at shrimp cleaners workers in pecan labuhan subdistrict medan labuhan district 2012. Skin disease is a health problem in Indonesia. According to data RISKESDAS (2007), the prevalence of dermatitis in Indonesia amounted to 6.78%, in North Sumatra at 2.63%. Based on data from Pekan Labuhan Community Health Center skin disorder cases 2011 in the district of Medan Labuhan many as 89 cases.The purposeof this studywas todetermine the relationship ofpersonal hygieneanduse ofsafety equipmenttoworkerscomplaintsof skin disorders inworkersatthe Pekan Labuhan Subdistrict Medan Labuhan District.This research is an analytic survey with a cross-sectional design, in order to know the relation between personal hygiene and use of safety equipment with complaints of skin disorders in workers at the Pekan Labuhan Subdistrict Medan Labuhan District 2012 with the population, as many as 75 people taken using the total sampling. The results of the chi-square variable age (p = 0.000), variable length work (p = 0.000), educational variables (p = 0.001), variable skin hygiene at work (p = 0.040), use of variable work clothes (p = 0.000) , the variable use of work gloves (p = 0.000) and the use of variable work shoes (p = 0.000), there is a significant association with symptoms of skin disorders. Variables that are not significant with symptoms of skin disorder is variable daily skin hygiene and cleanliness of the nails. Based on this research, for workers to pay more attention to personal hygiene and use of safety equipment in order to prevent occupational diseases. Keywords: personal hygiene, safety equipment, skin